The island [large type] - McKinty, Adrian (Little, Brown and Company, 2022)
"After moving from a small country town to Seattle, Heather Baxter marries Tom, a widowed doctor with a young son and teenage daughter. A working vacation overseas seems like the perfect way to bring the new family together, but once they're deep in the Australian outback, the jet-lagged and exhausted kids are so over their new mom. When they discover remote Dutch Island, off-limits to outside visitors, the family talks their way onto the ferry, taking a chance on an adventure far from the reach of iPhones and Instagram. But as soon as they set foot on the island, which is run by a tightly knit clan of locals, everything feels wrong. Then a shocking accident propels the Baxters from an unsettling situation into an absolute nightmare"--